Affective Social Ties—Missing Link in Governance Theory - van Winden, Frans; Justus Liebig University Giessen (My University, 2012)
Although governance is about interpersonal relationships, it appears that the antecedents and consequences of affective bonds (social ties) in social groups dealing with commonpool resources and public goods have been neglected. The welfare costs of the neglect of such bonds and their dynamic properties in economics are unclear but may be substantial. In this paper, I discuss a theoretical `dual process' social ties model and the behavioral experimental and recent neurological evidence this model has obtained. Furthermore, a number of implications and institutional issues are addressed.
Keywords: ddc:100; ddc:330